The essentials of face-to-face customer service (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. In this track, we are going to talk about face-to-face customer service, what it means and entails and why it is important. Some institutions and companies are only just opening up again to face-to-face interactions with customers and clients after a long period of remote working. It is essential that we are aware and reminded of key components of this type of customer-facing transaction to ensure a positive and productive experience for all concerned. What is face-to-face customer service? Although we can see faces and speak to each other via a screen, face-to-face means in person and physically present with the other person. At a time when it is so convenient to just log into Zoom or other communication software and hold calls, meetings, and training, why is face-to-face customer service so important? And how do we get it right? Learning Objectives Identify what face-to-face customer service is and how it differs from online customer service Examine the benefits of face-to-face customer service Discover the essentials of providing good face-to-face customer service.